ATRIBUSI KOMUNIKASI ORANG DENGAN HIV/AIDS (ODHA) KEPADA KERABAT DEKAT DI YOGYAKARTA - mugiarjo, mugiarjo (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
Regarding the response to self-disclosure, a person needs to make an attribution in order to know whether the response is really an intention or just a diversion. This article based on qualitative methods. Data collected by observation, interview, and documentation. The results of this study indicate that People Living With HIV/Aids (PLWHA) carry out quite strict regulations by conducting an assessment first before disclosing their Human Immunodeficiency Virus (HIV) status. The response obtained after they opened the status to the significant others was attributed by. The basis of sincere acceptance and response, the stability of the relationship between PLWHA and significant others after opening the status can be maintained, even stronger. PLWHA rely heavily on the power of spirituality to be able to build themselves better. In addition, the ability to make peace with oneself over their circumstances also influenced by this spirituality. Appreciation of spirituality also indicate that their engagement with God strengthened. This strength is shown by their awareness of the meaning of life.